ALDOL EQUILIBRATIONS OF UNPROTECTED TRIHYDROXYBICYCLIC LACTONES - ENANTIOMERIC TETRAHYDROXY-ALPHA-AMINOCYCLOPENTANE CARBOXYLIC-ACIDS FROM EPIMERIC BICYCLIC LACTONES - Hui, A; Fairbanks, A; Nash, R; Lilley, P; Storer, R; Watkin, D; Fleet, G (1994)
Six stereoisomers - including an enantiomeric pair - of 1-amino-2,3,4,5-tetrahydroxy-cyclopentane-1-carboxylate have been prepared from a single azidolactone starting material by a series of remarkable aldol equilibrations. © 1994.